Utilization of health services and its perceived barriers regarding infant care among tribal mothers in selected areas of West Bengal - Adhikari, Uma Rani; Paria, Chandrima (International Journal Of Community Medicine And Public Health, 2022)
Background: The tribal infant mortality rate in India was highest in the world among the indigenous populations. Utilization of child health services is poor in the tribal areas, due to presence of several barriers. The objective of the study was to assess the utilization of health services for infant, determining the perceived barriers of utilization of health services and finding the association between utilization of health services and selected socio-demographic characteristics. Methods: 100 mothers were selected by using purposive sampling technique. Self-developed tool was used for data collection after establishing validity and reliability. Data regarding participants’ profile was collected using a semi-structured interview schedule. To assess the utilization of health services, data were collected using record analysis proforma and semi structured interview schedule. A structured interview schedule was used to determine the perceived barriers of utilization of health services. Results: All mothers under the study utilized Institutional delivery and Immunization service for their children according to age. 65% of the mothers’ fully utilized health check-up service for their child during postnatal visit. Most of mothers (96%) received education for exclusive breast feeding for 6 months. Integrated Child Development Service was fully utilized by 74% mothers. Maximum (51%) of them fully utilized free treatment service for their children under JSSK. 63.46% mothers’ fully utilized Referral services. The study findings also show the presence of barriers among them like lack of awareness, lack of support person, financial barrier etc. Conclusions: Resolving the barriers to increase utilization of health services among tribal mothers is needed through improvement of their awareness.